PENERAPAN SISTEM PENCARIAN DAN PEMINJAMAN BUKU BERBASIS ANDROID PADA SMP N 3 SUNGAI AMBAWANG - Balbo, Florensius; Hoendarto, Genrawan; Tendean, Sandi (INTEKSIS, 2024)
This application is built consisting of two sides, namely, Android-based application users or book borrowers and a website-based server for librarians as admins. The android application will be used by borrowers in searching and borrowing books online, using students' personal smartphones, while the website application will be used by librarians to record books in the school library. The process of searching for books can be done on the android application, while the process of borrowing books can be done if the borrower is already a member of the library. In order to become a member of the library, borrowers must enter their personal data on the register page. The process of borrowing books can be done if the book you are looking for is available in the school library. In the android application students can borrow books, then they can take books to the school library section and the admin will confirm the status of borrowing books. The process of fines for borrowers of books can be carried out if the borrower exceeds the borrowing time limit set by the school library administrator and the process of paying the fine is carried out by visiting the school library directly, as well as returning the books being borrowed. The admin will confirm on the website server application the total fines and the fine payment process can be carried out. Likewise with the process of confirming borrowing, returning and renewing books which can only be done by the library admin. Keywords: Design, Search, Loan, Android, Libraries